2015
DOI: 10.5901/mjss.2015.v6n4s3p48
|View full text |Cite
|
Sign up to set email alerts
|

Managing Political Behavior of University Students

Abstract: The main objective of the institute of higher learning is to produce students who are excellence in academic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
1
0
1
Order By: Relevance
“…What they think sometimes extends beyond issues that have yet to occur. While the form of the political struggle of Malaysian students is more limited and restricted due to the existence of some constraints such as the Universities and University Colleges Act 1971 (UCCA), which has directly limited students' political freedom to fight for larger and global issues (Besar et al, 2015) Several studies at local institutions have also been conducted, with the education system identified as one of the factors contributing to the prevalence of demonstrations among university students. In a questionnaire research conducted on 300 informants among 21-year-old adolescents at UKM, they found a close relationship between the usage of the internet or social media and students' impressions of politics.…”
Section: Literature Reviewmentioning
confidence: 99%
“…What they think sometimes extends beyond issues that have yet to occur. While the form of the political struggle of Malaysian students is more limited and restricted due to the existence of some constraints such as the Universities and University Colleges Act 1971 (UCCA), which has directly limited students' political freedom to fight for larger and global issues (Besar et al, 2015) Several studies at local institutions have also been conducted, with the education system identified as one of the factors contributing to the prevalence of demonstrations among university students. In a questionnaire research conducted on 300 informants among 21-year-old adolescents at UKM, they found a close relationship between the usage of the internet or social media and students' impressions of politics.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sistem pendidikan di Amerika Syarikat dilihat berbeza dengan sistem pendidikan di Malaysia kerana pelajar-pelajar di Amerika Syarikat memang benar-benar merasakan bahawa politik kampus mempunyai hubungan yang sangat rapat dengan dunia politik nasional sehingga tuntutan yang mereka perjuangkan melibatkan isu yang besar termasuklah pembelaan ke atas pelajar yang kurang berkemampuan, serta isu sosial termasuklah menuntut agar ganja dan pengguguran dibenarkan oleh undang-undang di sana. Walaupun secara lahiriahnya, tuntutan mahasiswa Malaysia dilihat masih terikat dalam lingkungan kepentingan pelajar itu sendiri akibat daripada kekangan AUKU, namun tidak dapat dinafikan bahawa adanya tindakan sebahagian mahasiswa yang radikal dan melakukan protes membuktikan bahawa konfontrasi antara pihak kerajaan dengan mahasiswa tidak pernah reda sehingga ke hari ini (Junaidi et al, 2015).…”
Section: Kajian Literaturunclassified